A Randomized Controlled Trial Evaluating the Effects of Diosmin in the Treatment of Radicular Pain. (8th October 2017) - Wang, Yinhe; Fang, Xin; Ye, Lei; Li, Yishan; Shi, Hongfei; Cao, Yang
Abstract : Diosmin has been widely used to treat patients with vascular pain for its potent anti-inflammatory and analgesic effects. To evaluate the therapeutic effects of Diosmin in the treatment of radicular pain, we conducted an investigator-initiated, randomized, active-controlled noninferiority trial between January 1, 2009, and December 1, 2010. Diosmin (50 mg/kg/day) was orally administered to treat the radicular pain in 150 patients for one month. Another 150 patients with the same symptom were given 20% 250 ml mannitol (1 g/kg/day) for 7 days and dexamethasone (10 mg/day) for 3 days intravenously guttae. Short-term relief and long-term relief were measured. Secondary outcomes include improvement in functional and psychological status, return to work, and reduction in anti-inflammatory analgesic drugs intake. Patients treated with oral Diosmin achieved reduction in radicular pain. The total satisfaction rate of Diosmin group was 84.7% [95% confidence interval (CI): 77.9%, 90.0%], and the complete satisfaction rate was 50.7% (95% CI: 42.4%, 58.9%). No statistically significant difference was found between the Diosmin group and the active-control group regarding patient satisfaction. No adverse effects were found during the study period. Our study suggests that clinical application of Diosmin with a dose of 50 mg/kg/day might reduce the radicular pain. This trial is registered with ISRCTN97157037 .